Study of the Dual Resonant Frame Parametric Generator - Thuy, Dang Thi Thanh; Thuy, Luong Thi Minh (VNU Journal of Science: Mathematics - Physics; Vol 38 No 3DO - 10.25073/2588-1124/vnumap.4733, 2022)
We have built the research model of the dual resonant frame parameter generator based on the actual circuit diagram implemented in the laboratory to evaluate the mechanism of the dual resonant frame, two-frequency generator. The dual resonant frame parameter oscillator produces the desired frequency w 2 which depends on the pump frequency and frequency w 1 . On the basis of the research model, we have successfully tested the mechanism of the dual-frequency transmitter, which makes it possible to manufacture RF oscillators with low phase noise, thereby improving stability. The output frequency stability w 2 depends on the stability of the pump frequency and the frequency w 1 . Keywords: dual resonant frame, parametric generator system, pump frequency